A Systematic Review of Trends in US Attitudes toward Cannabis Legalization. (7th June 2022) - Chiu, Vivian; Hall, Wayne; Chan, Gary; Hides, Leanne; Leung, Janni
Abstract: Introductions: In the United States (US), support for cannabis legalization has increased over time. This study examines historical changes in legalization attitudes and the period-specific individual and external influences on these. Methods: A systematic search was conducted for publications in PubMed, EMBASE, and PsycINFO up to October 2019. Six studies with a regionally or nationally representative adult US-based populations were included. A secondary analysis was conducted using data from the National Survey of Drug Use and Health. Hierarchical age-period-cohort analysis assessed the trends in perceived harmfulness and availability of cannabis between 1996 and 2018. Ecological comparisons were made between these perceptions and support for cannabis legalization over time. Results: A steep growth in support for cannabis legalization began in the 1990s and continued to grow in a relatively linear manner. Most people developed more liberal views, with no evidence that changes within any one sociodemographic group was disproportionately responsible for the overall attitudinal change. Increases in the proportion of people who use cannabis, non-religious population and political liberalism may partially explain the increased support for legalization. The decline in perceived harmfulness of cannabis, as reflected in the media, may have contributed to the increased support for legalization. However, perceptions of the availability of cannabis remained stable despite significant relaxations in cannabis regulations. Conclusions: The US population has become more accepting of cannabis legalization. The attitudinal change is related to changes in the perceived risks and benefits of cannabis use, influenced by broader political and cultural changes over the study period.